Downstream merger with oligopolistic input suppliers - Lommerud, Kjell Erik,Straume, Odd Rune,Sørgard, Lars (online, 2002)
Abstract:
urn:nbn:de:0168-ssoar-112417
Keywords: (stw)Fusion; (stw)Lieferantenmanagement; (stw)Vertikale Integration; (stw)Oligopol; (stw)Gewerkschaft; (stw)Multinationales Unternehmen; (stw)Nash-Gleichgewicht; (stw)Theorie; (thesoz)Oligopol; (thesoz)Preisbildung; (thesoz)Wettbewerb; (thesoz)Wirkung; (thesoz)zwischenbetriebliche Kooperation; (thesoz)Fusion; (thesoz)Einfluss; (thesoz)Zulieferer; (thesoz)Unternehmen; (thesoz)Gewerkschaft; Arbeitspapier; Graue Literatur; Buch; Online-Publikation; Fusion; Lieferant; Vertikale Integration; Oligopol; Gewerkschaft; Multinationales Unternehmen; Nash-Gleichgewicht; Theorie